The Process of Human Capital Development in Accordance with Business Organization on Buddhism Approach in Phrae Province:A Case Study of Nimseeseng Company - Kittiwanno, Phrakru Sangharak Boonserm (Journal of International Buddhist Studies, 2016)
The human capital administration is a very important main point of organizational administration both public sector and private sector that has brought to the aim achievements, efficiency and successfully of the human capital administration. This research aimed to 1) study about the origin and development of the process of human capital development; 2) to study the operation of the process of human capital development; and 3) to study the replicating of organizational culture the process of human capital development in accordance with business organization on Buddhist approach in Phrae Province: a case study of Nimseeseng Company. It was a qualitative research by using interview and focus group discussion with the goal group. After participation in the operation of the process of human capital development, the results showed that; 1) the owner of business has brought knowledge from the Budhism to human capital development in his company and announced the policy and the vision of his company in the Buddhist administrative approach.; 2) the operations the process of human capital development in accordance with business organization on Buddhist approach in Phrae Province concerned about the mind, the training the Dhamma and ethnic and helping the society aspect; and 3) the replicating of organizational culture the process of human capital development in accordance with business organization on Buddhist approach in Phrae Province by giving the positive knowledge, the magazine, radio station, and VCD; and increasing the value and advance to the customer, the officer, and the community.